2010
DOI: 10.1111/j.1365-2702.2009.03092.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental management of childhood complaints: over‐the‐counter medicine use and advice‐seeking behaviours

Abstract: The use of over-the-counter medicines for symptom management is likely to increase with enhanced focus on self-care. It is important for all healthcare providers to proactively provide accurate, consistent and evidence-based information to parents regarding appropriate management of symptomatic and behavioural complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 49 publications
1
22
1
3
Order By: Relevance
“…They also found that use of acetaminophen and ibuprofen varied according to the age of the child, and that ibuprofen was not used before 6 months of age in their study sample. Trajanovska, Manias, Cranswick, and Johnston (2010) found that acetaminophen, choline salicylate, cough and cold preparations, and ibuprofen were the most commonly purchased OTC medications by parents for young children in their study. Although both studies found acetaminophen to be drug of choice in management of illnesses and injuries at home, it is also acknowledged to be the medication most frequently implicated in intentional and unintentional overdosing and liver toxicity (Balistreri & Van Hook, 2011;Bárzaga Arencibia & Choonara, 2012;Cohen, 2007).…”
Section: Preferred Analgesic/antipyretic Medicationmentioning
confidence: 95%
“…They also found that use of acetaminophen and ibuprofen varied according to the age of the child, and that ibuprofen was not used before 6 months of age in their study sample. Trajanovska, Manias, Cranswick, and Johnston (2010) found that acetaminophen, choline salicylate, cough and cold preparations, and ibuprofen were the most commonly purchased OTC medications by parents for young children in their study. Although both studies found acetaminophen to be drug of choice in management of illnesses and injuries at home, it is also acknowledged to be the medication most frequently implicated in intentional and unintentional overdosing and liver toxicity (Balistreri & Van Hook, 2011;Bárzaga Arencibia & Choonara, 2012;Cohen, 2007).…”
Section: Preferred Analgesic/antipyretic Medicationmentioning
confidence: 95%
“…Bien que la plupart des spécialités antipyrétiques soient en accès libre, les parents fondent leur choix sur les anciennes prescriptions médicales. Les informations relayées par les médias influencent également leur choix dans une moindre mesure [3,4,15,17,21,25]. Dans notre étude, la majorité des répondeurs pratiquaient l'alternance thérapeu-tique bien qu'elle ne soit pas recommandée et ceci plus encore en 2012 qu'en 2006.…”
Section: Discussionunclassified
“…Dans notre étude, la majorité des répondeurs pratiquaient l'alternance thérapeu-tique bien qu'elle ne soit pas recommandée et ceci plus encore en 2012 qu'en 2006. Les chiffres avancés par d'autres études sont très variables [9,14,17,25], mais il en ressort toujours que les parents utilisent l'alternance généralement sur avis médi-cal [4,17,[25][26][27][28][29][30][31]. Certaines études ont également suggéré que les parents utilisaient la bithérapie pour mieux maîtriser le niveau de la fièvre, contrôler la survenue de complication et limiter les risques d'effets secondaires ou de surdosage [21,25].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Teething symptoms in children can create much distress in parents [3,4]. Often, parents consult family or friends for advice on effective treatments as to alleviate their child's discomfort and pain [5]. It has been reported that the majority of parents (63-88%) manage teething symptoms using some form of over-the-counter (OTC) medication [3,6,7].…”
Section: Introductionmentioning
confidence: 99%